PERANCANGAN APLIKASI PENGARSIPAN SURAT PROGRAM STUDI SISTEM INFORMASI PADA SEKOLAH TINGGI TEKNOLOGI INDUSTRI PADANG MENGGUNAKAN VB NET 2010 - Veni Wedya Wati; Elma wati (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2018)
Archive is defined as a place to storage important scripts or documents. In general, archive is a form of  writing in form of document in any media that has a historical value or liability so that can be stored. Manual letter archive system and not systematic report logs cause searching the document difficult and time-consuming. Therefore, it is necessary to design an application to help the head of the study program in search of reports of letters in and out.